PENGARUH PENGGUNAAN BAKTERI Rhodobacter DENGAN DOSIS YANG BERBEDA TERHADAP KUALITAS AIR PEMELIHARAAN IKAN LELE - Fajrianti Dwi Kurnia; Nanda Diniarti; Fariq Azhar (Universitas Sriwijaya, 2022)
Traditional and intensive cultivation activities on freshwater fish species that have economic value have been carried out, one of which is catfish. One way to increase the amount of catfish production can be done by increasing the stocking density in the rearing container. Increased stocking density of catfish rearing can cause problems in water quality. This study aims to analyze the administration of Rhodobacter bacteria on the quality of catfish rearing water and conclude the best dose for catfish rearing water quality. This research was carried out for 60 days starting from May-July 2021 at the Wet Laboratory, Aquaculture Study Program, Faculty of Agriculture, Mataram University. This study used an experimental method with a completely randomized design (CRD) which included 4 treatments and 3 replications. The treatments consisted of A (without giving Rhodobacter), B (Adding Rhodobacter 0.5 ml/1 liter of water), C (adding Rhodobacter as much as 1 ml/1 liter of water), D (adding Rhodobacter as much as 1.5 ml/1 liters of water). The highest ammonia content was found in treatment A of 8.78 mg/L and the lowest was in treatment D of 4.78 mg/L. The highest nitrite content was found in treatment A of 1.26 mg/L and the lowest was found in treatment D of 0.41 mg/L. The highest nitrate content was found in treatment D of 73.33 mg/L and the lowest was found in treatment A of 40.00 mg/L. The highest survival rate was in treatment D of 95.83% and the lowest was in treatment A of 71.7%.